Short-term effects of pack animals grazing exclusion from Andean Alpine Meadows - Barros, Ana Agustina; Pickering, Catherine Marina; Renison, Daniel (Arctic, Antarctic, and Alpine Research)
Grazing by livestock can have positive, neutral, and/or negative effects on vegetation depending on the intensity and type of grazing. This includes grazing by pack animals used for tourism in mountain protected areas. We assessed the response of vegetation to the exclusion of grazing by pack animals over one growing season in the highest park in the Southern Hemisphere, Aconcagua Provincial Park, dry Central Andes. Twenty pairs of exclosures and unfenced quadrats were established in three high-altitude Andean alpine meadows that are intensively grazed by horses and mules used by commercial operators to transport equipment for tourists. Vegetation parameters, including height, cover, and composition were measured in late spring when exclosures were established and ~120 days later at the end of the growing season along with above-ground biomass. Data was analyzed using mixed models and ordinations. Vegetation responded rapidly to the removal of grazing. Vegetation in exclosures was more than twice as tall, had 30% more above-ground biomass, a greater cover of grasses including the dominant Deyeuxia eminens, and less litter than grazed quadrats. These changes in the vegetation from short-term exclusion of grazing are likely to increase the habitat quality of the meadows for native wildlife. Fil: Barros, Ana Agustina. Griffith University; Australia Fil: Pickering, Catherine Marina. Griffith University; Australia Fil: Renison, Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Investigaciones Biológicas y Tecnológicas. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina